Mise-en-Scene as (pre)text; an insistence on a negotiated space for the creating of new theatre works - Newton, Larissa Ann (Michaelis School of Fine Art, 2016)
The purpose of this exploration is to reflect on the activity of writing for performance, with the focus specifically on the generation of the dramatic text, and to further the notion of mise en scene as prescribed by Pavis. (Pavis, 1983: 25) This is in relation to the making of a new South African play entitled Reach, written by myself, Lara Foot Newton and directed by Clare Stopford. The exploration looks at a model of theatre making where the writer is present during the rehearsal phase. I propose that there is a pre-mise en scene, which exists as pre(text) for the dramatic and performance texts. This pre - mise en scene pre-figures or alludes to the possible "object of knowledge u (Pavis, 1983 : 25) before its manifestation. This pre - mise en scene is the first encounter with the negotiated space of writing for theatre ; of writing the dramatic text ; of a first writing of the performance. The exploration is divided into three parts: Part 1. Mise en scene as ( pre)text. A network of associations which are negotiated into the dramatic text. With reference to Pavis ((Pavis, 1983 : 25) and Brook (Brook, 1993 : 52) Part 2 : Mise en scene as (p r e)text and the dramatic text. The co-dependent relationship which exists between mise en scene as (pre)text and the writing of the dramatic text within a negotiated space. With reference to Harold Pinter, in his Nobel prize lecture in 2005 entitled Art, Truth and Politics where he describes how sound, light and dialogue collude to give birth to character in relation to his two plays The Homecoming and Old Times ) Part 3 : Mise en scene as (pre)text, the dramatic text and the performance text. The relationship which exists between mise en scene as (pre)text and the dramatic text, and mise en scene in relation to possible meaning and interpretation within the performance text. With reference to the notion of dramaturgy (Meyrick, 2006 : 281) and to workshopped plays by director Barney Simon.